32x+3=40x-3

Simple and best practice solution for 32x+3=40x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32x+3=40x-3 equation:


Simplifying
32x + 3 = 40x + -3
Reorder the terms:
3 + 32x = 40x + -3
Reorder the terms:
3 + 32x = -3 + 40x
Solving
3 + 32x = -3 + 40x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-40x' to each side of the equation.
3 + 32x + -40x = -3 + 40x + -40x
Combine like terms: 32x + -40x = -8x
3 + -8x = -3 + 40x + -40x
Combine like terms: 40x + -40x = 0
3 + -8x = -3 + 0
3 + -8x = -3
Add '-3' to each side of the equation.
3 + -3 + -8x = -3 + -3
Combine like terms: 3 + -3 = 0
0 + -8x = -3 + -3
-8x = -3 + -3
Combine like terms: -3 + -3 = -6
-8x = -6
Divide each side by '-8'.
x = 0.75
Simplifying
x = 0.75

You can always share this solution

See similar equations:

| 4x-16=24 | | 15-4x=x-5 | | (8x-10+8x-10)+(6x+6x)= | | 250+16x=210+18x | | 15d-8=2d | | (36x^2)-120=-70 | | 5h+2g=23 | | -14.8+0.2s=-16.4s+19.85+18.7s | | 8-5(2a+3)= | | y=-9-2x | | 8z-1=3z+6 | | |3-2b|=-7 | | |3-2b|=7 | | 8-y=5 | | 70x-35=245 | | 5x+12-2x=36+6x-7x | | -4(x+2)-11=2(-2x-3)-14 | | -15.73-9.3b=16.82-7.2b | | x-3x-150=0 | | 3y+48y=0 | | 3.9k=2.1k+17.1 | | 8=3x+4x-6 | | 11(p-5)-10(6p+22)=-32+38 | | -4y-15=0 | | -2.6r=1.7r+18.92 | | n-9=162 | | (5x+5x)+(3x+6+3x+6)= | | t^2+3t-40=0 | | a+17=4 | | 3*y-7=27 | | 19.4-.6c=-16.6 | | -7x-x=-11-2x | | 9(b-4)-7=5(3b-2) | | 8x-3=104 | | 5=2*n-3 | | x+2+3x= | | 19.4-.6c=16.6 | | 19.9g+13.35=-4.2g-13.2-5.4g | | 4x+2x-5=-2x+5+6 | | 40d=20+60d | | -49=6-13-4c | | 9*3-(-6)+7= | | 4x-10=7x-13 | | 3*4-7=27 | | A=3xa-5 | | 6(m-4)=24 | | 14v+10v+17=-11+10v | | 50x^2+5y^2-20x+25y-23=0 | | 8x+16=6x-18 | | 4x+10=7x+13 | | -2(t-2)+4t=6t-8 | | 8m=210 | | 2*x-4=23 | | -4(3x-5)=3-(8x+7) | | 6x+2x=-48 | | 6+10y=4y | | x-7(5x)=113 | | 3x+3-1=3x+2 | | 2(x-2)+5x= | | 2(x+4)+4=4x-2(-4+x) | | 16+36X-2X-2X+12=4(23) | | 9*3+-6+7= | | 16-2n=10 | | 6f+11=-2f-13 | | 3b+4.4=6.2-6b |


Related pages


4x 3y 6graph y 2 3x 1gcf generatorttu webworklcm solverroman numeral 812cosx 1finding the gcf calculatorgraph 2x 4y 8roman numerals convert800-580factor by gcfsquare root of 12.5prime factorization of 48 using exponentsgreatest common factor of 1201-0.010.8 inches to fraction1234567890 0987654321greatest common factor of 48 and 547x 5 5xadding simple fractions calculator3x2 8x 4206-2003x 4y 6solving linear equations calculatorgcf of 63 and 4299 roman numeralsr2hadding subtracting fractions calculatorfactorization of 84mdt solution2x 1y7y 6fraction times fraction calculatorgraph of cos 3xprime factorization for 2161952 in roman numeralssquare root of 245 simplifiedlowest common denominator calculator fractionsdifferentiate cos 2x2l 2wbxdxcommon multiples of 4 and 8y 3sin 2xfactoring with x 32001 roman numerals0.125 in fractionwhat is the prime factorization of 44factoring equations solver190-13what is the lcm of 7log10x 332 qt galwhat is the lcm calculatorax2 bx c 0factorization of 12065-3017x4table of prime factorsformula of 1 cos2xfactors of49find the prime factorization of 245sin2x cos2x 0common multiples of 9least common denominator finderwhat is the prime factorization of 125 using exponentspercentages decimals120.25graph y 3 2x9v to 6vfactorization calculator1960 in roman numeralstan15prime factorization for 144what is the prime factorization of 188sqrt 196solve 2x y 73x2 5x 2roman numerals vx